Sintesis Arang Aktif Dari Tandan Kosong Kelapa Sawit Dengan Aktivator Asam Fosfat - Jumadi Sihotang, Antonius (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
Indonesia is the largest palm oil producing country in the world. Every ton of processed oil palm fruit yields approximately 230 kg of empty fruit bunches (EFB). Currently, only about 10% of the EFB generated by the palm oil industry is utilized, while the rest remains as waste. This has prompted researchers to explore ways to optimize its use, one of which is converting EFB into activated charcoal.. The aim of this study is to examine the effect of phosphoric acid concentration on the quality of activated charcoal made from EFB. The research consists of two main processes: the carbonization of EFB and the activation of the resulting charcoal using phosphoric acid as an activating agent. The concentrations of phosphoric acid used for activation were 6M, 7M, 8M, 9M, and 10M.. Based on the results, the activated charcoal produced at all acid concentrations met the Indonesian National Standard (SNI 06-3730-06). The best quality activated charcoal was obtained using 10M phosphoric acid, with quality parameters including a moisture content of 7.76%, ash content of 6.55%, and an iodine adsorption capacity of 1,011.60 mg/g.